Beneficiation of the Nechalacho rare earth deposit: Flotation response using benzohydroxamic acid. (December 2016) - Jordens, Adam; Marion, Christopher; Grammatikopoulos, Tassos; Hart, Brian; Waters, Kristian E.
Highlights: Kinetic behaviour of multiple REM measured in the presence of hydroxamic acid (Bz). Bz is a more effective collector for REM with higher solubility and higher REE content. A secondary addition of Bz improves flotation of important REM (zircon). Impact of lead ions on REM recovery determined by TOF-SIMS. Two different reagent schemes proposed for industrial processing of the deposit. Abstract: Rare earth minerals (REM) may be beneficiated using a variety of separation techniques with froth flotation being the most commonly applied in operating REM separation plants. Many different collectors have been tested with traditional REM such as bastnäsite. The most successful are the hydroxamic acids. The Nechalacho deposit contains many REM for which there is minimal processing information in literature. Thus, experimental investigation into their flotation behaviour is required. This work focuses on understanding the effect of a benzohydroxamic acid collector on the flotation of a REM enriched pre-concentrate from the Nechalacho deposit (after lab-scale gravity and magnetic separation steps). The lab-scale flotation response of the REM is quantified using mass recoveries, water recoveries, QEMSCAN and chemical assay data and TOF-SIMS in order to study the recovery, entrainment and kinetics of different REM. Three different flotation schemes are investigated to determine the effect of a secondary addition of collector as well as the addition of lead ions, a known activator in hydroxamic acid flotation. It is important to note that the goal of this work is to determine fundamental flotation properties of the different REM in the Nechalacho deposit. As such, the process investigated here is not indicative in any way of the current process design for this deposit.